THE AMMONITE GENUS GAUDRYCERAS FROM THE SANTONIAN–CAMPANIAN OF ANTARCTICA: SYSTEMATICS AND BIOSTRATIGRAPHY (Ameghiniana, 2016)
Belying previous interpretations on its rarity in southern latitudes, Gaudryceras de Grossouvre is well represented in the Santonian– Campanian of Antarctica. The study of more than 300 specimens from the Santa Marta, Rabot and Snow Hill Island Formations designates five species that characterize four successive stratigraphic intervals: 1) Gaudryceras cf. G. strictum, Santonian, Alpha Member, lower part of the Santa Marta Formation; 2) Gaudryceras santamartense sp. nov., Santonian–early Campanian, Alpha Member, lower mid part of the Santa Marta Formation; 3) Gaudryceras brandyense sp. nov., late early Campanian–?basal mid Campanian, Beta Member, upper part of the Santa Marta Formation; and 4) Gaudryceras cf. G. mite and Gaudryceras rabotense sp. nov., mid Campanian–late Campanian, upper middle part of the Rabot Formation and lower part of the Hamilton Point Member of the Snow Hill Island Formation. There are two differently ornamented neanoconchs characterized by exhibiting dense or sparse strong flares, which are features of taxonomic importance at the specific level. In Antarctica, Gaudryceras is well represented from the Santonian to the mid Campanian, rare in the late Campanian and not known in the Maastrichtian. Such facts strongly contrast with data recorded outside Antarctica, particularly in the North Pacific, where Gaudryceras is well represented up to the late Maastrichtian. A striking biogeographical contrast is apparent for the Antarctic gaudryceratids. That is, while the early Campanian Gaudryceras brandyense sp. nov. and the mid–late Campanian G. rabotense sp. nov. are apparently restricted to Antarctica, the Santonian–early Campanian Antarctic species are very similar or co-specific to widely distributed forms.Resumen. EL GÉNERO DE AMONITES GAUDRYCERAS DEL SANTONIANO–CAMPANIANO DE ANTÁRTIDA: SISTEMÁTICA Y BIOESTRATIGRAFÍA. El género Gaudryceras está bien representado en el Santoniano–Campaniano de la Antártida contradiciendo interpretaciones previas sobre su raro registro en altas latitudes australes. Se estudiaron más de 300 ejemplares pertenecientes a las formaciones Santa Marta, Rabot y Snow Hill Island concluyendo la existencia de cinco especies que caracterizan cuatro intervalos estratigráficos sucesivos: 1) Gaudryceras cf. G. strictum, Santoniano, Miembro Alpha, parte inferior de la Formación Santa Marta; 2) Gaudryceras santamartense sp. nov., Santoniano–Campaniano temprano, Miembro Alpha, parte media inferior de la Formación Santa Marta; 3) Gaudryceras brandyense sp. nov., Campaniano temprano tardío– ?Campaniano medio basal, Miembro Beta, parte superior de la Formación Santa Marta; y 4) Gaudryceras cf. G. mite y Gaudryceras rabotense sp. nov., Campaniano medio–Campaniano tardío, parte media superior de la Formación Rabot y parte inferior del Miembro Hamilton Point, Formación Snow Hill Island. Las neanoconchas de estas especies presentan características de importancia taxonómica a nivel específico caracterizadas por dos estilos marcadamente diferentes de ornamentación, fuertes costillas densas o espaciadas. En la Antártida, Gaudryceras está bien representado desde el Santoniano hasta el Campaniano medio, es raro en el Campaniano tardío, y no se conoce para el Maastrichtiano. Esto está en fuerte contraste con el registro fuera de Antártida, donde Gaudryceras está bien representado hasta finales del Maastrichtiano. Los gaudrycerátidos antárticos evidencian un marcado contraste biogeográfico, mientras que Gaudryceras brandyense sp. nov., Campaniano temprano, y G. rabotense sp. nov., Campaniano tardío, aparentemente se restringen a la Antártida, las especies antárticas del Santoniano–Campaniano temprano son muy similares o co-específicas con formas ampliamente distribuidas.